Answer:
=x^2+2x+5
Step-by-step explanation:
X^2+2x+5-0
=X^2+2x+5+0
Combine Like Terms:
=X^2+2x+5+0
=(X^2)+(2x)+(5+0)
=X^2+2x+5
Hope this helped!
I'm afraid you're wrong. We may divide 24 by 8 to find out how long does it take for Alejandra to husk 1 ear of corn and then just divide 33 by the result:
24 ÷ 8 = 3
So Alejandra husks 1 ear of corn in 3 minutes.
33 ÷ 3 = 11
Answer: In 33 minutes Alejandra can husk <u>11 ears of corn</u>.
1. y+5=-x-5
2. y=-x-5-5
3.y=-x-10
4. y=x-10
_______________________
1. distribute negative sign
2. move the constant to the right and change the sign
3. -5-5 equals -10, bring everything down
4. change the sign of the x to positive, the equation is in standard form